EcoCleanzyme Wash, Inovasi Sabun Cuci Piring Berbasis Ecoenzyme dan Proses Pembuatannya - Mirah Sandika; Elany Tri Yuliyanti; Shila Radasahila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
EcoCleanzyme Wash is an innovative dishwashing liquid based on ecoenzyme, a liquid derived from the fermentation of organic waste such as fruit peels, vegetable scraps, brown sugar, and water. This product offers an environmentally friendly solution for household needs while addressing the challenges of suboptimal organic waste management. The three- month ecoenzyme fermentation process produces a liquid rich in natural enzymes with antibacterial, antifungal, and insecticidal properties, capable of breaking down harmful organic compounds. EcoCleanzyme Wash provides a safer alternative compared to conventional dishwashing liquids, which often contain harmful chemicals that can pollute water and soil. This product not only effectively cleans utensils but also supports the concept of sustainability by utilizing household organic waste. Additionally, EcoCleanzyme Wash helps reduce environmental pollution, often caused by improperly managed household waste. In Indonesia, organic waste constitutes the largest portion of household waste, which, if left unmanaged, can contaminate water, soil, and air, leading to various health issues such as diarrhea and skin infections caused by pathogenic microorganisms. The use of ecoenzyme in EcoCleanzyme Wash represents a tangible step toward promoting the concepts of reuse and sustainable waste management, aligned with government regulations on waste handling. This product also contributes to reducing negative impacts on ecosystems and raising public awareness about the importance of managing organic waste. This research aims to provide a detailed guide on the production process of ecoenzyme-based dishwashing liquid, covering the utilization of organic raw materials, fermentation steps, and product formulation. It is expected that the findings of this research can serve as a reference for the development of other environmentally friendly products and encourage innovation in household waste management. EcoCleanzyme Wash is a progressive step in creating a product that not only fulfills household needs but also positively impacts the environment.